Bond strength prediction model of defective grout materials in half-grouted sleeve connections under uniaxial and cyclic loadings. (17th October 2022) - Liu, Qizhou; Lin, Yuhan; Li, Jinzhou; Yang, Chengjian; Chen, Jingyi; Zhang, Min; Liu, Bing
Highlights: The influence mechanism of defects on the grout stress transfer path and sleeve restraint effect was analyzed. The influence of different loading modes and defect distribution on the failure probability and performance index of the grouted sleeves was investigated. The mathematical expressions for the deterioration law of bond performance between defective grout materials and reinforcing bars were derived. A prediction model for the bond strength between defective grout materials and reinforcing bars under uniaxial and cyclic loading conditions is developed. Abstract: The grouted sleeve connection is one of the most popular approaches to connect the reinforcing bars in the prefabricated structures. Insufficient grouting defects of sleeve connections significantly could decrease the bond strength of the grout materials; therefore, increase the failure risk of connection joints. To obtain a prediction model for the bond strength between reinforcing bars and grout materials under uniaxial tensile and cyclic loading conditions is essential for the design and construction. The stress transfer path of the defective grout material and its restraint effect of the sleeve were analyzed in terms of the uniaxial tensile and cyclic loading tests on ninety-nine specimens of half-grouted sleeves with defects. The mechanism was illustrated through the tests and the performance indicators of the connection joints and the deterioration of the grout bonding strength were quantified as a model. The defect-induced instability in the sleeve restraint system is one of the most significant reasons which leads to the bond deterioration in grout materials with defects. Under the same conditions, a concentrated and laterally distributed defect will cause a more severe deterioration than a uniformly dispersed defect. Compared to uniaxial tension, with the defect rate over 30%, the cyclic loading significantly amplifies the adverse effect of defects on the bond performance; however, if a defect rate is less than 20%, the loading methods will not influence on the bond performance of the grout materials. A prediction model for the bond strength is proposed with consideration of the restraint of the sleeve and the properties of the grout itself. Comparing with a large amount of test data, the predicted results can match well with the test results when the defect rate is less than 40%. The proposed work can provide the guidance for the performance assessment of defective grouted sleeves in both seismic and non-seismic zones.